Mapping the Paths from Styles of Anger Experience and Expression to Obsessive–Compulsive Symptoms: The Moderating Roles of Family Cohesion and Adaptability - Liu, Liang; Liu, Cuilian; Zhao, Xudong (Frontiers in Psychology, 2017)
Previous research has shown strong connections of anger experience and expression with obsessive-compulsive (OC) symptoms. Additionally, studies have demonstrated links between family environment variables and OCD. Our study aims to integrate the perspectives from these two literatures by exploring the moderating roles of family cohesion and family adaptability in the relationship between anger proneness and suppression and OCD symptoms. A total of 2008 college students were recruited from a comprehensive university in Shanghai, China between February and May 2016. The subjects completed self-report inventories, including the Symptom Check List-90, State-Trait Anger Expression Inventory 2 (Chinese version) and Family Adaptability and Cohesion Scale, second edition (Chinese Version). Controlling for age, one-child family status, ethnicity, family income, current depression and anxiety, our analyses showed that the association between anger proneness and OC symptoms was moderated by family cohesion among men and that family adaptability moderated the connection between anger suppression and OC complaints among women. The findings imply that a more cohesive and empathic family environment may protect male students with high levels of anger proneness from developing OC behaviors or thoughts. The results suggest that for female subjects who are accustomed to suppressing angry feelings, flexible family coping strategies and communication atmospheres would reduce their vulnerability to OC symptoms. The findings are somewhat consistent with those of previous studies on psychotherapy outcomes that showed that OCD patients benefitted from psychotherapeutic interventions that cultivated the clients’ family cohesion and adaptability.